Key texts in human geography - Hubbard, Phil; Kitchin, Rob; Valentine, Gill 1965- (SAGE, 2008)
A unique resource for students, 'Key Texts in Human Geography' provides concise but rigorous overviews of the key texts that have transformed post-war human geography.